Do Termination Provisions Truncate the Takeover Bidding Process? - Audra L. Boone; Mulherin, J. Harold (Review of Financial Studies, 2007)
[We provide new evidence on termination provisions and the takeover bidding process. Our central contribution is a novel database from Securities and Exchange Commission (SEC) documents that accurately measures the incidence of termination provisions and the depth of competition in takeover deals. We show that biased data in prior research produced incorrect conclusions on the relation between termination provisions and judicial decisions, bidder toeholds, and deal size. Our comprehensive data also show that termination provisions are positively related to takeover competition. Our evidence is consistent with the information/commitment hypothesis in which termination provisions do not truncate bidding but instead culminate the takeover process.]